Study of amino acids in raw materials Mirabilis jalapa l. - Goriacha, Lilia; Zhuravel, Iryna; Sarray, Dhurgham Khalid Abed (Annals of Mechnikov’s Institute, 2021)
Introduction. Amino acids are biologically active substances (BAS) that play an important role in the normal functioning of the body. Some amino acids have been used to prevent and treat pathologies of various systems and organs. One source of amino acids is plants. It is known that due to the formation of complexes of amino acids with other BAS increases their digestibility and potentiates the pharmacological effect. A promising plant for the production of herbal medicines with multi-vector pharmacological activity is Mirabilis jalapa L., the raw material of which has long been used in folk medicine as an antimicrobial, antiparasitic, reparative, anti-inflammatory, tonic. Data on the amino acid composition of four o’clock in the literature are quite limited, so it was important to conduct its study. Material & methods. The objects of the study were selected grass, leaves, stems, flowers, fruits and roots of four o’clock, harvested in the Kharkiv region (Ukraine) during 2019-2020. The amino acid composition of the raw material of four o’clock was studied on an automatic amino acid analyzer AAA T-339M by ion exchange liquid column chromatography. Results & discussion. As a result of the study of the amino acid composition in the herb, leaves, stems, flowers and roots of four o’clock, 18 amino acids were identified, and 17 amino acids in fruits. Amino acids in the raw material of four o’clock accumulated mainly in the roots, flowers, leaves and herb, in fruits and stems their content was much lower. In the roots, flowers, leaves and herb of four o’clock, glutamic acid prevailed among the identified amino acids, the content of which was 3.91 g / 100 g, 2.86 g / 100 g, 2.23 g / 100 g and 1.24 g / 100 g respectively. γ-Aminobutyric acid and cystine were the minor components in the amino acid composition of almost all studied species of four o’clock. Conclusion. For the first time, the amino acid composition of raw four o’clock was studied. As a result of the study it was found that a significant predominance of amino acid content was observed in the roots of four o’clock (27.10 g / 100 g). Stems (2.11 g / 100 g) and fruits (3.49 g / 100 g) accumulated the least amount of amino acids. Glutamic acid was predominant in almost all subjects. The obtained results can be used in the preparation of herbal medicines based on raw four o’clock. DOI: 10.5281/zenodo.5499674